Effect of boundary conditions of the underlying soil layer on the seismic response of dikes - Filbert (2016)
Earthquake is one of the factors that cause the failure of a dike. During an earthquake, there are lot of effects from each elements of soil that contributed to the failure of a dike and one of which is boundary layer condition. Therefore, this study aims to investigate the effects of boundary layer condition of underlying soil on the seismic response of dike by using Plaxis 2D software. The peak grade acceleration (PGA) and total displacement at the crest of dike were the main interest in this study. These outputs were obtained by making a dike structure and applying absorbing and fixed boundary condition to four different shapes (horizontal, trapezoidal, staircase and multi-layer) of soil basin and simulate it with harmonic acceleration and Ferndale earthquake. The results showed that dike model in fixed boundary condition has higher horizontal PGA and maximum vertical displacement than fixed boundary condition. These results were probably due to the absorbed increment of stresses induced by the absorbing boundary condition. The limitations and future recommendations are further discussed in the paper.